Rågångsproblematik i avverkningsplanering hos Norrskog - Svensson, Markus (SLU/School for Forest Management, 2016)
This study deepens in the subject of property boundaries. The focus lies on the problems that occur during the logging design when the boundary is not properly maintained. The study was done in collaboration with the forest owners association, Norrskog. The purpose has been to see if there is a problem, and if so, how big is the problem, and finally what the reason is for that. Methods used in this study includes interviews, a sample and time studies. The study has shown that many property boundaries are poorly maintained and that this is a problem in the logging design , in particular private forestry.